Data Mining Algorithm for Physical Health Monitoring of Young Students Based on Big Data. (12th May 2021) - Sun, Jiangang; Jiang, Xiaoran; Yuan, Guoliang; Chen, Zhenhuai
Abstract : With the continuous improvement of living standards, the level of physical development of adolescents has improved significantly. The physical functions and healthy development of adolescents are relatively slow and even appear to decline. This paper proposes a novel data mining algorithm based on big data for monitoring of adolescent student's physical health to overcome this problem and enhance young people's physical fitness and mental health. Since big data technology has positive practical significance in promoting young people's healthy development and promoting individual health rights, this article will implement commonly used data mining algorithms and Hadoop/Spark big data processing. The algorithm on different platforms verified that the big data platform has good computing performance for the data mining algorithm by comparing the running time. The current work will prove to be a complete physical health data management system and effectively save, process, and analyze adolescents' physical test data.